The Officiality of The Master and Margarita: A Study of the Relationship Between Bulgakov and Soviet Authorities - Wang, LanTing; Zhang, RongQi; Dinara Valeeva; Yuan, ChunHong (International Theory and Practice in Humanities and Social Sciences, 2025)
The study of the creative process behind The Master and Margarita is inseparable from an examination of Bulgakov's literary career—particularly his relationship with Soviet authorities. Stringent literary censorship undoubtedly profoundly influenced Bulgakov's character creation and plot construction in The Master and Margarita. The novel, which originated in the late 1920s, was the result of an arduous creative process spanning over a decade, during which the narrative underwent numerous transformations. Thanks to the relatively well-preserved archives and materials related to Bulgakov, the creative journey of this masterpiece by one of the 20th century's most enigmatic Russian writers can be almost fully reconstructed. Through the novel's tumultuous publication history, we can glimpse, from various deleted fragments, the concessions the work had to make to align with official ideology. The interplay between internal literary development and external censorship mechanisms is directly reflected in the literary work itself.